2013
DOI: 10.1136/bmj.f3726
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of monovalent rotavirus vaccine in Bolivia: case-control study

Abstract: Objective To evaluate the effectiveness of two doses of a monovalent rotavirus vaccine (RV1) against hospital admission for rotavirus in Bolivia.Design Case-control study.Setting Six hospitals in Bolivia, between March 2010 and June 2011.Participants 400 hospital admissions for rotavirus, 1200 non-diarrhea hospital controls, and 718 rotavirus negative hospital controls. Main outcome measuresOdds of antecedent vaccination between case patients and controls; effectiveness of vaccination ((1-adjusted odds ratio)×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 28 publications
4
38
1
1
Order By: Relevance
“…The literature describing the burden of rotavirus in Bolivia has demonstrated the effectiveness of rotavirus vaccine in the region. 5,6,14,16,17 Seven years before vaccine introduction at this study site, rotavirus was detected by PCR in 24% of 317 children aged < 5 years hospitalized with AGE. 17 Rotavirus prevalence was 36% when children < 2 years were analyzed separately, nearly double the prevalence described here (19%).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The literature describing the burden of rotavirus in Bolivia has demonstrated the effectiveness of rotavirus vaccine in the region. 5,6,14,16,17 Seven years before vaccine introduction at this study site, rotavirus was detected by PCR in 24% of 317 children aged < 5 years hospitalized with AGE. 17 Rotavirus prevalence was 36% when children < 2 years were analyzed separately, nearly double the prevalence described here (19%).…”
Section: Discussionmentioning
confidence: 98%
“…Higher relative norovirus prevalence in this age group may be because of greater reductions in rotavirus infections in children aged < 12 months after vaccine introduction; however, rotavirus vaccine in Bolivia has demonstrated similar efficacy in both children under and above 12 months. 12,14 Asymptomatic norovirus infections were very common. Children infected with norovirus are known to shed the virus for several weeks to months after both symptomatic and asymptomatic infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Besides the need to assess different rotavirus vaccine choices, several studies have improved what is known about diarrheal diseases and rotavirus vaccine efficacy and effectiveness in different settings around the world. 6,[10][11][12][13][14][15][16][17] Despite the effectiveness, safety, cost-effectiveness and World Health Organization (WHO) recommendations to introduce RV1 or RV5, 18,19 most countries have not yet introduced the vaccine, most of these in Africa and Asia. As of August 5, 2014, 68 countries have introduced RV1/RV5 in their Expanded Programs on Immunizations (EPI) schedules.…”
Section: Estimated Cost-effectiveness In Global Vaccinementioning
confidence: 99%
“…Several candidate rotavirus vaccines (RIT4237, WC3, RRV and RRV-TV) had lower or no measureable efficacy in clinical trials in South America and Africa compared with Europe and North America [1]. More recent studies with new licenced vaccines, Rotarix and Rotateq, have shown lower efficacy and effectiveness in developing countries in Asia, Africa and Latin America [2][3][4][5][6]. The OPV has also faced challenges in the developing world.…”
Section: Introductionmentioning
confidence: 99%